2019
DOI: 10.5999/aps.2018.01382
|View full text |Cite
|
Sign up to set email alerts
|

Proximal ligation after the side-to-end anastomosis recovery technique for lymphaticovenous anastomosis

Abstract: Background Lymphaticovenous anastomosis is an important surgical treatment for lymphedema, with lymphaticovenous side-to-end anastomosis (LVSEA) and lymphaticovenous endto-end anastomosis being the most frequently performed procedures. However, LVSEA can cause lymphatic flow obstruction because of regurgitation and tension in the anastomosis. In this study, we introduce a novel and simple procedure to overcome this problem. Methods Thirty-five female patients with lower extremity lymphedema who underwent lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This result suggested that the retrograde shunt may not be corrected after the surgery. Intraoperative conversion of the STE to ETE anastomosis by ligation of proximal lymphatic vessel was reported in previous studies for management of retrograde venous-lymphatic flow in STE anastomosis in LVA [7,8]. Retrograde venous flow is found relatively frequently in patients with lymphedema.…”
Section: A a B B C C D Dmentioning
confidence: 89%
“…This result suggested that the retrograde shunt may not be corrected after the surgery. Intraoperative conversion of the STE to ETE anastomosis by ligation of proximal lymphatic vessel was reported in previous studies for management of retrograde venous-lymphatic flow in STE anastomosis in LVA [7,8]. Retrograde venous flow is found relatively frequently in patients with lymphedema.…”
Section: A a B B C C D Dmentioning
confidence: 89%
“…There are few case reports describing the application of side-to-end lymphaticovenous anastomoses and the advantages such as overcoming the size discrepancy. [16][17][18] Yamamoto et al and AlJindan et al reported comparative analysis showing that side-to-end lymphaticovenous anastomosis may have better results compared to endto-end lymphaticovenous anastomosis, but most of the findings were limited to early-stage lymphedema and failed to further explore the difference in outcome for different International Society of Lymphology stages. 17,19 Considering that the valvular dysfunction worsens as the lymphedema progresses, a comparative analysis is warranted between the different International Society of Lymphology stages of lymphedema patients.…”
mentioning
confidence: 99%